The transcriptome of wild-type and immortalized corneal epithelial cells - Kai Furuya (Nature Portfolio, 2021)
Measurement(s) Molecular Profiling Technology Type(s) RNA sequencing Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14093807